Influence of phenols on growth and membrane permeability of free and immobilized Escherichia coli. - Heipieper, H J (1991)
The inhibition of the exponential growth of Escherichia coli K-12 by different phenolic compounds was examined. Cells entrapped in calcium alginate showed a greater tolerance than cells grown in suspension. The extent of inhibition of growth of the immobilized cells depended on the period of growth in the gel matrix. After the addition of bacteriostatic concentrations of phenol or 4-chlorophenol, a dose-dependent efflux of metabolites such as ATP and of K+ ions was elicited. Provided that glucose was supplied as an energy substrate, a reaccumulation of K+ ions at low phenol concentrations was observed. The restoration of the membrane gradient for K+ always preceded the continuation of growth in the presence of the toxic compounds. Compared with free cells, those cells immobilized and grown in alginate suffered a smaller loss of cations after the addition of 4-chlorophenol. The reestablishment of gradients was observed at higher concentrations of the pollutants with entrapped cells than with free cells. Corresponding to the increase in tolerance, the membrane damage was reduced in cells grown in immobilized form for longer times. These data offer a mechanistic explanation of the protection of immobilized microorganisms from phenolic solvents. The data point to the membrane as an important cell component in the toxicity of these pollutants.